2004
DOI: 10.1366/0003702042641272
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Visible and Near-Infrared Spectroscopy as a Tool for Assessing Fiber Fineness during Mechanical Preparation of Dew-Retted Flax

Abstract: Flax fiber must be mechanically prepared to improve fineness and homogeneity of the sliver before chemical processing and wet-spinning. The changes in fiber characteristics are monitored by an airflow method, which is labor intensive and requires 90 minutes to process one sample. This investigation was carried out to develop robust visible and near-infrared calibrations that can be used as a rapid tool for quality assessment of input fibers and changes in fineness at the doubling (blending), first, second, thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 11 publications
0
9
0
Order By: Relevance
“…It is obvious that the Tex values of fibers are consistent with the results of degumming rate of RF assisted water retting presented above. Compared to the spinning flax fiber fineness of 4.02 tex in the work conducted by Sharma and Reinard (2004), the 6 d-90 • C and 10 d-90 • C treated fiber yielded reasonable fineness values.…”
Section: Linear Densitymentioning
confidence: 64%
“…It is obvious that the Tex values of fibers are consistent with the results of degumming rate of RF assisted water retting presented above. Compared to the spinning flax fiber fineness of 4.02 tex in the work conducted by Sharma and Reinard (2004), the 6 d-90 • C and 10 d-90 • C treated fiber yielded reasonable fineness values.…”
Section: Linear Densitymentioning
confidence: 64%
“…Traditionally water‐retted fibres lose the residual colour of the retted stems, as a result of a combined action of wind, rain and sun, during wetting and drying of the stooks (bundle of retted stems) in open fields (Dujardin, 1948). The fineness of the samples ranged between 46.75–71.70 dtex (Table 4), which indicated that the experimentally water‐retted fibres were coarse compared with a fineness range of 35.34–56.5 dtex for scutched and hackled water‐retted fibres reported by Sharma & Reinard (2004).…”
Section: Resultsmentioning
confidence: 80%
“…The leverage, outlier detection, ratio of calibrated to validated explained variance, ratio of validated to calibrated explained variance and total explained variance limits during the calculation were set at 3.0%, 3.0%, 0.5% and 0.75%, and 20%, respectively. The spectra obtained from an extensive sample set of dew‐retted and water‐retted fibres taken from mechanical fibre preparation lines (Sharma & Reinard, 2004) were employed to develop NIR (1100–2500 nm) equation for predicting fibre fineness.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…(2000) used diffuse refl ectance FT-IR and other techniques to study the surfaces of modifi ed sisal. Sharma and Reinard (2004) explored the potential of visible and near IR spectroscopy as a tool for the rapid quality assessment of fl ax fi bres during the spinning process. They successfully focused on assessment of the quality of input fi bre and changes in fi neness at all stages from the doubling (blending) through to the roving stage.…”
Section: Spectroscopic Methodsmentioning
confidence: 99%